Fascin overexpression is associated with higher grades of breast cancer - Abbasi, Ata; Noroozinia, Farahnaz; Anvar, Samira; Abbasi, Mohammad; Hosseinzadeh, Sonia; Mokhtari, Seyed (Polish Journal of Pathology, 2019)
In the present study, we tried to evaluate the relationship between Fascin molecule expression and other histopathologic parameters, especially tumor grade and hormone profile. Sixty-one malignant breast tumors were enrolled in this study. Fascin marker staining was performed on paraffin blocks of breast samples using immunohistochemistry (IHC) method. The age range of patients was 26-87 years, with an average of 48.41 ±1.68. Our results showed that fascin expression was significantly higher in tumors with high grade histology, lymph node involvement and larger tumor size (p = 0.04, 0.04, 0.04, respectively). Also fascin expression in triple negative tumors was significantly higher than other molecular subtypes (p = 0.001). fascin can be used as an important marker in evaluating breast cancer especially in triple negative tumors.